2008
DOI: 10.1103/physrevlett.101.077002
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Behavior in Compressed SolidSiH4with a Layered Structure

Abstract: The electronic and lattice dynamical properties of compressed solid SiH4 have been calculated in the pressure range up to 300 GPa with density functional theory. We find two energetically preferred insulating phases with P2(1)/c and Fdd2 symmetries at low pressures. We demonstrate that the Cmca structure having a layered network is the most likely candidate of the metallic phase of SiH4 over a wide pressure range above 60 GPa. The superconducting transition temperature in this layered metallic phase is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 18 publications
4
80
1
Order By: Relevance
“…(ii) what is the physical origin behind the anomalous superconducting transition behavior in experiment? Many independent works have predicted the insulating I41/a structure to be the most stable phase from 50 to 220 GPa, 6,10,11 while experiments presented a P6 3 structure. 14 Moreover, as alluded above, the P6 3 structure of silane is dynamically unstable in this pressure range and is energetically quite unfavorable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) what is the physical origin behind the anomalous superconducting transition behavior in experiment? Many independent works have predicted the insulating I41/a structure to be the most stable phase from 50 to 220 GPa, 6,10,11 while experiments presented a P6 3 structure. 14 Moreover, as alluded above, the P6 3 structure of silane is dynamically unstable in this pressure range and is energetically quite unfavorable.…”
mentioning
confidence: 99%
“…The particular interesting is the case of silane (SiH 4 ), which was predicted to have at least seven phases. 10,11 Only one solid phase has been reported in the pressure range between 10 and 25 GPa with a monoclinic structure at room temperature. 12 At pressure above 60 GPa, Chen et al 13 found the pressure-induced metallization for silane by analyzing the infrared reflectivity data at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, after subsequent geometry re-optimization of the distorted structure we arrive at a structure of F dd2 symmetry (this structure has been previously reported in Refs. [11] and [12]) which exhibits a 2 + 2 + 2 coordination with two short (terminal) Si-H bonds and four longer (bridging) ones. Thus the coordination of Si by H is in a form of a distorted octahedron with every octahedron linked to another four by four of its corners.…”
Section: Phonon-guided Optimizationmentioning
confidence: 99%
“…Previous theoretical studies [11][12][13][14][15][16] were concentrated on establishing the structure of the claimed metallic form of silane. For this a wide range of strategies of screening the potential energy surface (PES) of this system have been employed: chemical intuition [13], procedure of random sampling [14], molecular dynamics [15] and evolutionary algorithm [16].…”
Section: Introductionmentioning
confidence: 99%